KONSEP PERENCANAAN PARTISIPATIF DUSUN LONGSERANG DESA LANGKO KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT SEBAGAI DUSUN WISATA EDUKASI TENTANG ALAM DAN PRODUKSI GULA SEMUT - Liza Hani Saroya Wardi; Barzian Ali Kitab; Ismail Adha; Emi Sukmana; Dwi nilam sari la unga; Bayu Aji; Mulhan Hadi; Zulyana Tus Timor; Ekhi Adrianti; Ade Rachmat s. Malik; Ikhsan Ramadhani (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to create a planning concept for the hamlet of Lonserang Barat Utara Langko Village, Lingsar District, West Lombok Regency as an educational tourism hamlet about nature and the production of ant sugar. The planning for the North West Longserang hamlet of course contains activities for collecting data and information about the potential and problems of the hamlet along with the thoughts of the community so that what is envisioned for the progress of the hamlet can be achieved so that it becomes an educational tourism hamlet. The method used is the PRA method with various analyzes in it, namely descriptive analysis in the form of SWOT analysis, situation analysis and participative analysis, while the analysis carried out is evaluation analysis in the form of root problem analysis, fishbone analysis, goal analysis, project alternative analysis with data collection carried out using interview methods, observation, photo mapping. Through this planning, it is hoped that changes will occur in the North West Longserang hamlet in the form of social, cultural, physical, economic and environmental changes, which in the end will lead to better changes, especially in efforts to improve the welfare of the North West Longserang community, which so far is still considered not yet prosperous and advanced. because their human resources are still low.